Cardiovascular risk among men with and without erectile dysfunction: case-control study. (12th October 2011) - Jun, Chen; Bin, Zhang; Tao, Qi; Bo, Wang; Xiaoming, Li; Chen, Chen
Abstract : Objective: There is growing evidence of a link between erectile dysfunction (ED), metabolic syndrome (MS) and cardiovascular disease (CVD). The study was to evaluate cardiovascular risk through the Framingham cardiac risk score (FCRS) criteria, C-reactive protein (CRP) assays and presence of metabolic syndrome (MS) in men with and without erectile dysfunction diagnosed in andrological clinic. Design and setting: A retrospective case-control study was conducted. The patients were selected from a healthcare program at the Third Affiliated Hospital of Sun Yat-Sen University between January and December 2009. Methods: Three hundred and forty two men, with a mean age of 50.3±3.9 years (range, 31–65 years), were retrospectively selected, and they were divided into two groups: men with ED (n=171) as diagnosed by international index of erectile function score and men without erectile dysfunction (n=171). Differences of MS prevalence, CRP and FCRS were analysed and the two groups were compared. Results: The presence of metabolic syndrome was significantly greater among men with erectile dysfunction than that among men without ED (39.18% vs 18.71%, p<0.01). The CRP levels were significantly higher among men with ED than that among men without ED (0.18±0.033 mg/dl vs 0.04±0.012 mg/dl, p<0.01). Patients with erectile dysfunction also had high FCRS (13.9±1.4 vs 8.8±2.3, p<0.01). CRP and FCRS did not correlate with the severity of erectile dysfunction. The severity of erectile dysfunction was directly associated with metabolic syndrome. Conclusion: Men with erectile dysfunction presented higher cardiovascular risk according to the presence of metabolic syndrome, FCRS and CRP.